The durable effect of acupuncture for episodic migraine: a systematic review and meta-analysis - Shi, Hangyu; Miao, Runyu; Gao, Shuai; Zhu, Lili; Fang, Jiufei; Liu, Zhishun (Frontiers in Neuroscience, 2023)
Background Migraine is a common and recurrent type of headache. Avoiding trigger factors is not often successful in reducing headache frequency, duration, and severity. Prophylactic medications may be effective but are limited by strict indications and daily medication intake. This review aimed to investigate the durable effect of acupuncture on episodic migraine. Methods Seven databases including Medline, Embase, PubMed, etc., were searched for English and Chinese literature from their inception to 23 November 2022. Two independent reviewers screened the retrieved studies and extracted the data. Primary outcomes were monthly migraine days, monthly migraine attacks, and VAS score at 3 months post-treatment. The risk of bias in included studies was assessed using the Cochrane Risk of Bias 2.0 tool. Meta-analysis was conducted where applicable. Results Fifteen studies were included in this review. Acupuncture reduced the number of migraine attacks (MD -0.68; 95% CI –0.93, −0.43; p < 0.001), the number of days with migraine (MD –0.86; 95% CI –1.18, −0.55; p < 0.001), and VAS score (MD –1.01; 95% CI –1.30, −0.72; p < 0.001) to a greater degree than sham acupuncture at 3 months after treatment. Significant differences in reducing pain intensity of migraine in favor of acupuncture compared with waitlist (MD –1.84; 95% CI –2.31, −1.37; p < 0.001) or flunarizine (MD –2.00; 95% CI –2.35, −1.65; p < 0.001) at 3 months after treatment were found, and the differences reached the minimal clinically important difference (MCID). Conclusion This review found that the durable effect of acupuncture for episodic migraine lasted at least 3 months after treatment. More high-quality studies with longer follow-up periods in the future are needed to confirm the findings.